A Critical Technology Implementation of Sodium Solid-state Battery as the Secure Long-Duration Energy Storage toward the Terra-Watt Grid Projects - Kurniadi, Tedi; Fahri, Mirad; Aurellia, Fidela; Nurrosyid, Naufan (Indonesian Scholar Society, 2022)
The current lithium-ion battery (LIB) has become a vital technology for realizing a highly-productive society. The current system can be found easily in every personal electronic device, such as smartphones, laptops, smartwatches, and digital cameras. However, the future of LIBs is questionable due to the scarcity and security issues. The common electrolytes in this system are highly flammable, toxic, and easy to leak. Thus, inherit them to be applied for more mass-reliable energy sources, the terra-watt projects. Therefore, the development of an all-solid-state battery based on earth-abundant and cost-effective processing should be carried out immediately to dominate the market and for future civilization. Herein, we promoted a Sodium solid-state battery (SSB) that potentially be a key in energy storage technology due to its mechanical properties, electrochemical stability, high ion conductivity, and robust cyclic performance. Furthermore, a five-year direct implementation strategy of SSB was also presented, constructed from sodium and chromium electrodes.